Single dose delta‐9‐tetrahydrocannabinol in chronic pancreatitis patients: analgesic efficacy, pharmacokinetics and tolerability. (17th January 2016) - de Vries, Marjan; Van Rijckevorsel, Dagmar C. M.; Vissers, Kris C. P.; Wilder‐Smith, Oliver H. G.; Van Goor, Harry
Abstract : Aim: We aimed to assess the analgesic efficacy, pharmacokinetics, tolerability and safety of a single dose of Δ9‐THC in patients with chronic abdominal pain resulting from chronic pancreatitis (CP). Methods: This was a randomized, single dose, double‐blinded, placebo‐controlled, two way crossover study in patients suffering from abdominal pain as result of CP ( n  = 24), post hoc subdivided into opioid and non‐opioid users. Δ9‐THC (8 mg) or active placebo (5 mg/10 mg diazepam) was administered orally in a double dummy design. Results: No treatment effect was shown for delta VAS pain scores after Δ9‐THC compared with diazepam. Δ9‐THC was well absorbed with a mean t max of 123 min. No significant differences were found between Δ9‐THC vs . diazepam for alertness, mood, calmness or balance. Feeling anxious and heart rate were significantly increased after Δ9‐THC compared with diazepam. The most frequently reported adverse events (AEs) after Δ9‐THC administration were somnolence, dry mouth, dizziness and euphoric mood. Conclusions: A single dose of Δ9‐THC was not efficacious in reducing chronic pain resulting from CP, but was well tolerated with only mild or moderate AEs. The PK results in CP patients showed delayed absorption and an increased variability compared with healthy volunteers.